Community preparedness towards dam disaster: Disaster Risk Reduction (DRR) program in Cameron Highlands - Muda, Rahsidi Sabri; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Abdullah, Fatin Shahira (2021)
Dam disaster occurrences are an unexpected event that occurs suddenly without warning. It has become very alarming, resulting in a catastrophic break followed by a flood wave at high speed with considerable loss of life and catastrophic damages to infrastructure and the environment. Given these circumstances, the community preparedness for disaster risk reduction (DRR) is important to strengthen disaster response strategies. It helps the community to understand the situations to face disaster and interact with present conditions with efficient manners. The research aims to investigate the community awareness and preparedness and the effectiveness of the DRR program toward dam-related disaster. In this research, two dams in Cameron Highland have been selected as sites study: Sultan Abu Bakar (SAB) Hydroelectric Scheme and its vicinity in Lembah Bertam; and Susu Dam and its vicinity in Pos Telanok. The research utilised questionnaire surveys as a data collection method, where Statistical Package Software SPSS Version 25 was used to analyse data. The finding indicates that an integrated community-based program is an effective approach to increase people's preparedness for the disaster. The result can assist local agencies and dam owners in formulating strategies for future DRR programs. Identifying these pertinent factors enables a greater understanding of the community's preparedness for disaster risk reduction (DRR) in both dams of Cameron Highlands.